Petrophysical properties of crystalline rocks - Harvey, P. K. (Geological Society, 2005)
Boreholes are commonly drilled into crystalline rocks to evaluate their suitability for various applications such as waste disposal (including nuclear waste), geothermal energy, hydrology, sequestration of greenhouse gases and for fault analysis. Crystalline rocks include igneous, metamorphic and even some sedimentary rocks. This volume covers the following aspects of the petrophysical properties of crystalline rocks: fracturing and deformation, oceanic basement studies, permeability and hydrology, and laboratory based studies.
"This volume is the result of the meeting sponsored by the Borehole Research Group of the Geological Society of London"--Preface
Keywords: Crystalline rocks -- Congresses.; Crystalline rocks -- Analysis -- Congresses.; Petrology -- Congresses.; elektronické knihy; electronic books